Dampak Abrasi dan Banjir Rob Terhadap Tingkat Kesejahteraan Masyarakat Pesisir di Desa Pantai Bahagia, Kecamatan Muara Gembong, Kabupaten Bekasi - Bestari, Nanda Raka; Dirgayusa, Gusti Ngurah Putra; Darmendra, Putu Yogi (Journal of Marine Research and Technology; Vol 7 No 2 (2024): OKTOBER 2024, 2024)
Coastal areas are very vulnerable and affected by environmental degradation, such as shoreline changes, abrasion, mangrove erosion, marine pollution, and other disasters. This study aimed to determine the relationship between abrasion and tidal flood disasters with the welfare level of the Pantai Bahagia Village coastal community. The research method was conducted using a case study method with descriptive analysis with 99 respondents and using key informants for data reinforcement through in-depth interviews. Indicators of community welfare levels use indicators from the Central Statistics Agency (BPS), including Income, Expenditure, Education, Health, Living Conditions, Living Facilities, and Ownership of Residence. The results of this study obtained the value of the welfare level of the coastal community of Pantai Bahagia Village before abrasion and tidal floods had a high welfare level category (score 15-21) with a value weight of 17 with all respondents having a high level of welfare after abrasion and tidal floods hit Pantai Bahagia Village, the level of community welfare decreased with a moderate welfare level category (score 9-14) with a value weight of 14, 79 respondents were remaining in the high welfare category, and 20 respondents were in the moderate category. It may be due to the loss of the primary source of livelihood of the Pantai Bahagia Village Community, namely ponds that were damaged due to abrasion and tidal floods. At the same time, there is an increase in the amount of expenditure every year, so the amount of expenditure is more significant than income. Besides that, health and community housing conditions have also decreased due to abrasion and tidal floods over the past five years.